Serum cholesterol concentrations in yearling bulls - Goldy, G.; Olsen, W.; Riley, Jack G. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A wide range in serum cholesterol concentrations was observed within and between all four breeds of yearling bulls studied. The significance of this observation is unknown at this time. Addition research is necessary to determine the heritability of serum cholesterol, and the relationship between serum cholesterol of sires and the tissue cholesterol of their progeny.
Keywords: Beef; Serum cholesterol; Yearling bulls; Heritability